Prescription Patteerns and Medication Adherence of Antimicrobials of Diabetic Patients in Department of General Surgery at Tertiary Care Hospital (Asian Journal of Pharmaceutics (AJP), 2025)
Objective: This prospective observational study aimed to analyze the prescribing patterns and medication adherenceof antimicrobials in diabetic foot patients in the department of general surgery at a tertiary care hospital. A total of120 diabetic foot patients were assessed in this study for the period of 6 months. This study mainly describes aboutthe antimicrobial usage and current prescription patterns of antimicrobials in patients of diabetic foot ulcer (DFU).By empowering patients to understand the rationale behind their treatment regimens and the consequences ofnon-adherence, healthcare providers can enhance patient engagement and promote self-management. Medicationadherence is effectively measured by Morisky Medication Adherence Scale 8-item (MMAS-8). Purpose of theStudy: The purpose of this study is to analyse the prescribing patterns and medication adherence of antimicrobialsin diabetic foot patients in the department of general surgery. Evaluating the antimicrobial usage by MMAS-8.Methods: This study was carried out in a tertiary care teaching hospital located in South India, over 6 monthsfrom October 2023 to March 2024. The study assessed the antimicrobial usage in the management of DFU,current prescription patterns of antimicrobials, and Medication adherence. Conclusion: In conclusion, thisstudy provided insights into prescribing patterns and medication adherence in diabetic foot patients receivingantimicrobial therapy, aiding the understanding of DFU management. Variations in prescription patterns highlightthe need for standardized guidelines to optimize treatment and minimize antimicrobial resistance risks. Improvingmedication adherence and patient education is crucial for better clinical outcomes and reduced healthcare burdenassociated with diabetic foot complications.